THE CONCEPT OF “ORDER” IN SPAIN (1770-1870) - Chacón Delgado, Pedro José (Revista de Historia Social y de las Mentalidades, 2024)
The concept of ‘order’ permits an investigation  into not only the disposition of the components  of a political space such as Spain during  the period under question (1770-1870), but  also how political actors perceived the space  in which they moved. Within this period  there was a substantial change in what had  previously been regarded as the natural  order as established by God, as a result of  the events which led to the approval of the  1812 Constitution. From this point onwards  the political scene underwent a profound  transformation, with the appearance of  the intellectual elites, in opposition to the  defenders of the Old Regime, as well as the  first inklings of social revolution, within a  context of continual changes of constitution  and government, virtually until the Restoration  of 1875. The concept of order also clashes with  the concept of liberty, as the juxtaposition of  both definitions was the real key of political  debate throughout 19th-century Spain.
Keywords: natural law; order; constitution; conceptual history